Ketamine but not glycine potentiates antidepressant like action of citalopram in mice exposed to chronic mild stress - Verma, Veena; Sanone, Pankaj P.; Mehta, Ashish K.; Tripathi, Chakra D. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: The present study was designed to investigate the effect of citalopram, ketamine, glycine and their combinations on animal models of depression. Methods: Swiss Albino male mice were subjected to chronic mild stress for 6 weeks for inducing depression, and randomly divided into different groups: citalopram (5 and 10 mg/kg), ketamine (17.5 and 35 mg/kg), glycine (50 and 100 mg/kg), ketamine (17.5 mg/kg) + citalopram (5 mg/kg) and ketamine (17.5 mg/kg) + glycine (50 mg/kg). Two behavioural tests were utilized for the assessment of depression, namely tail suspension test (TST) and forced swim test (FST). Immobility time was recorded for 6 min, before and after administration of drug. Results: Citalopram (10 mg/kg) administration caused significant decrease in the immobility time in TST model only but not in FST. Citalopram (5 mg/kg) and ketamine (17.5 mg/kg) caused insignificant decrease in immobility time in both the models. Moreover, ketamine in combination with Citalopram significantly reduced the immobility time in both the models. Glycine at a dose of 100 mg/kg (but not 50 mg/kg) significantly increased the immobility time in both the models as compared to control group. Further, ketamine when administered with glycine caused increase in the immobility time on both the paradigms, though insignificant. Conclusions: Ketamine demonstrated antidepressant like action in both TST and FST models. Moreover, it potentiated the antidepressant effect of citalopram that might be due to the role of NMDA receptors.